Artificial Intelligence-Assisted Colonoscopy With or Without Mucosal Exposure Device for Detection of Colorectal Adenomas: A Meta-Analysis - Beran, Azizullah; Nayfeh, Tarek; Ramai, Daryl; Albakri, Almaza; Saleem, Nasir; Spadaccini, Marco; Hassan, Cesare; Repici, Alessandro; Guardiola, John J.; Rex, Douglas K. (Endoscopy International Open, 2025)
Artificial intelligence (AI) and mucosal exposure devices like Endocuff have independently improved the adenoma detection rate (ADR) during colonoscopy. This meta-analysis evaluated the combined effect of Endocuff and AI versus AI alone on colorectal neoplasia detection rates.We searched PubMed, Embase, and Web of Science for randomized controlled trials (RCTs) comparing the impact of Endocuff+AI versus AI alone on colorectal neoplasia detection. Primary outcome was ADR; secondary outcomes included advanced adenoma detection rate (AADR), sessile serrated lesion detection rate (SSLDR), cecal intubation time, and withdrawal time. Pooled risk ratios (RRs) and mean differences (MDs) with 95% confidence intervals (CIs) were calculated using a random-effects model.Three RCTs with 2404 subjects were included (n = 1198 Endocuff+AI vs. n = 1206 AI alone). ADR was significantly higher in the Endocuff+AI group than in the AI alone group (54% vs. 48%, respectively) (RR 1.12, 95% CI 1.03–1.21, P = 0.01, I2 = 0%). There was a trend toward higher AADR (12.3% vs. 10%, RR 1.23, 95% CI 0.96–1.59, P = 0.10, I2 = 17%) and SSLDR (17.6% vs. 15.5%, RR 1.16, 95% CI 0.96–1.40, P = 0.13, I2 = 0%) in the Endocuff+AI group compared with the AI alone group, but it did not reach statistical significance. Both cecal intubation time (MD -0.61 minutes; 95% CI -1.54–0.33; P = 0.20; I2 = 87%) and withdrawal time (MD -0.42 minutes; 95% CI -1.01–0.17; P = 0.17, I2 = 60%) were similar between the two groups.Endocuff combined with AI was superior to AI alone in improving the adenoma detection rate without increasing intubation or withdrawal times.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; Quality and logistical aspects; Quality management; CRC screening